2016
DOI: 10.1186/s12889-016-3438-6
|View full text |Cite
|
Sign up to set email alerts
|

How are self-rated health and diagnosed disease related to early or deferred retirement? A cross-sectional study of employees aged 55-64

Abstract: BackgroundMore people will probably continue working into old age in the future due to the increased size of aging populations in many countries. We therefore need to know more about older workers’ health in relation to their work situation and retirement. This study is a part of a theoretical development of older workers’ situations. Older workers’ situations are theoretically themed in nine areas by the authors of this study. The aims of the study were to investigate the relationship between: i) diagnosed di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 37 publications
2
47
1
Order By: Relevance
“…Good health is one of the most important factors for inclusion in working life [6] [12] [15] [36] [37]. Health decrease with biological ageing as people get older, but the variation is huge [38] [39].…”
Section: Retirementmentioning
confidence: 99%
See 1 more Smart Citation
“…Good health is one of the most important factors for inclusion in working life [6] [12] [15] [36] [37]. Health decrease with biological ageing as people get older, but the variation is huge [38] [39].…”
Section: Retirementmentioning
confidence: 99%
“…[10] [11] [12] [15] and on a theoretical model (the swAge model, www.swAge.org) regarding factors of importance for a sustainable work life participation. The quotation from the interviews gives a deeper understanding for the older employees' situation and of the managers' attitude to their older employees.…”
mentioning
confidence: 99%
“…Another limitation is regarding the self-reporting and that the health problems by that is subjective and not objectively reported. However, earlier studies stated that subjectively reported self-rated health is a better predictor than objective diagnosed health problems to the possibility of an extended working life and also to death by the health problems [31,32].…”
Section: Limitationsmentioning
confidence: 94%
“…Those nine areas is also described in the theoretical swAge-model (Sustainable working life for all ages) and are: 1) self-rated health, diagnoses, function variation; 2) physical work environment; 3) mental work environment; 4) work schedule, work pace, recuperation; 5) private economy; 6) private social environment; 7) work social environment; 8) work tasks, stimulation, motivation, self-crediting; 9) knowledge, skills, competence. Good health is a very important factor to whether people are able to work, or to take sick leave or some form of retirement (1,(7)(8)(9)(10)(11)(12). Poor physical work environment and work conditions increase the risk of work accidents, leave people worn out and push them to leave working life early (1,(7)(8)(9)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%